From feed to fork: immunity, performance and quality of products from farm animals fed sugarcane products - Edirisinghe, Nee; Flavel, Matthew; Pouniotis, Dodie; Zakaria, Rosita; Lim, Kosta Fremielle; Dias, Daniel Anthony (Frontiers in Animal Science, 2024)
Sugarcane extracts have generated a growing interest due to their potential applications that extend beyond conventional sugar and ethanol production. These by-products, along with sugarcane extracts offer nutrients and compounds that can be utilized in animal feed supplementation, aiming to improve immunity and growth performance, and the quality of animal-derived products consumed by humans. The immune-boosting properties of sugarcane supplementation have been documented through several studies highlighting enhanced cytotoxicity, increased phagocytic capacity, and modulation of immune cells and cytokine production. Abundant in polyphenols and bioactive compounds, sugarcane products are believed to contribute to these immunological effects. However, further research is required to unravel the specific mechanisms underlying these actions. Supplementing sugarcane by-products in animal feed has shown promising results of improved growth rates and weight gains in various animal species. Sugarcane supplementation positively influences animal performance by optimizing nutrient intake and utilization, enhancing feed conversion efficiency, and promoting healthy growth. Moreover, sugarcane supplementation has been associated with improved meat tenderness and overall quality in animal-derived products. To optimize the utilization of sugarcane products, future research will need to focus on determining optimal inclusion quantities and product or extract combinations, identifying specific compound classes, and balancing nutritional profiles in animal feed formulations. Studies should focus on evaluating long-term effects on animal health and subsequent product quality, and explore the environmental sustainability of sugarcane product supplementation in feed. This mini-review explores the impact of sugarcane product supplementation on swine, poultry, aquaculture species and ruminants, focusing on immunity, growth performance, and product quality.